Extração de ferro da cera de carnaúba utilizando sistemas microemulsionados - Fontana, Josilma Fátima (2011)
The constant search for biodegradable materials for applications in several fields shows that carnauba wax can be a viable alternative in the manufacturing of biolubricants. Carnauba wax is the unique among the natural waxes to have a combination of properties of great importance. In previous studies it was verified the presence of metals in wax composition that can harm the oxidative stability of lubricants. Considering these factors, it was decided to develop a research to evaluate iron removal from carnauba wax, using microemulsion systems (Me) and perform the optimization of parameters, such as: extraction pH, temperature, extraction time, among others. Iron concentration was determined by atomic absorption and, to perform this analysis, sample digestion in microwave oven was used, showing that this process was very efficient. It was performed some analysis in order to characterize the wax sample, such as: attenuated total reflectance infrared spectroscopy (ATR-IR), thermogravimetry (TG), differential scanning calorimetry (DSC), energy dispersive X-ray fluorescence (EDXRF), scanning electron microscopy (SEM) and melting point (FP). The microemulsion systems were composed by: coconut oil as surfactant, n-butanol as cosurfactant, kerosene and/or heptanes as oil phase, distilled water as water phase. The pH chosen for this study was 4.5 and the metal extraction was performed in finite experiments. To evaluate Me extraction it was performed a factorial design for systems with heptane and kerosene as oil phase, also investigating the influence of temperature time and wax/Me ratio, that showed an statistically significant answer for iron extraction at 95% confidence level. The best result was obtained at 60°C, 10 hours contact time and 1: 10 wax/Me ratio, in both systems with kerosene and heptanes as oil phase. The best extraction occurred with kerosene as oil phase, with 54% iron removal